Self-Efficacy with Anxiety Levels of Diabetes Mellitus Patients in Hospital Care Settings - Afandi, Alfid Tri; Putri, Prestasianita; Darmawan, Taufan Citra; Wijaya, Cipta Perdana (Jurnal Ilmiah Kesehatan, 2024)
Clients with diabetes mellitus often experience anxiety in taking medication. This can interfere with the treatment process, reducing the mechanism of the treatment being carried out. This study aims to analyze the relationship between client self-efficacy and anxiety levels when taking treatment at the hospital. This study uses a quantitative design with a cross-sectional approach. The sample in this study consisted of 133 respondents, and the sampling technique used was consecutive sampling. Data collection used the DMSES (Diabetes et al.) and HADS (Hospital Anxiety and Depression Scale) questionnaires. The results showed that the p-value = 0.001 and r = - 0.693. This indicates that there is a relationship between self-efficacy and the level of anxiety of patients with diabetes mellitus and has a negative correlation; namely, the higher the self-efficacy, the lower the anxiety level of the respondents. It is hoped that these results can serve as a record for both patients and health workers so that they pay more attention to each other's health and so that health workers, especially nurses, are expected to be able to assess the level of anxiety experienced by patients with Diabetes Mellitus.